Controlling anthracnose and postharvest quality of papaya (Carica papaya L. CV. frangi) using Bacillus subtilis strain B34 - Hasan, Md. Fakhrul (2012)
Papaya (Carica papaya L.), a climacteric fruit, is highly vulnerable to several postharvest diseases. Among them, anthracnose caused by Colletotrichum gloeosporioides is the major postharvest disease which demands an effective control. This study was carried out aiming at developing an eco-friendly biocontrol agent to control the disease. Three antagonistic bacteria identified as B34, B60 and B71 were screened from 81 epiphytic bacteria isolated from leaf and fruit surfaces of papaya. These three isolates were identified as Bacillus subtilis based on Biolog Omniliog Gen III identification system and its 16S rDNA sequence which was compared with the related bacteria in the GenBank. All the three strains were proved to be efficacious for the control of anthracnose of papaya in in vitro biocontrol assays. Bacterial strain B34,B71 and B60 produced antibiotic substances which restricted the fungal growth up to 84.6, 80.6 and 79.3%, respectively compared with the control. Moreover, these strains not only able to completely inhibit the fungal growth by secreting diffusible antibiotics but also restricted 40.6, 33.4, and 34.6% of fungal growth through the antibiotic volatiles produced by strains B34, B60 and B71, respectively. In spore germination test,germination percentage decreased gradually with increased concentrations of strains’ suspension. No spores of the test fungus germinated at the concentration of 108 CFU mL-1 but the performance of strain B34 was quite better than B71 and B60 at lower concentration. Mycelial growth of C. gloeosporioides was completely absent in 108 CFU mL-1 cell suspensions of all strains. On the other hand, strain B34 showed statistically highest inhibition of growth of mycelial plug in sterilized culture filtrate treated plates compared to strain B60 and B71. However, in vitro performances of B. subtilis strain B34 against C. gloeosporioides showed its better efficacy compared to strains B60 and B71. The growth of strain B34 was faster in nutrient broth medium and the biomass production reached the highest level in temperatures between 30-36ºC three days after incubation. The strain B34 showed its different mechanisms in controlling C. gloeosporioides by reducing nutrients for test fungus, producing proteolytic enzymes and secreting antibiotics to quash the cell wall as well as dissolve the fungus. Moreover, strain B34 was able to attack and degrade the hyphae of pathogen when observed under scanning electron microscope. This bacterium was found to be highly compatible with 20% Aloe vera gel (aloe gel) and 2% sodium bicarbonate (SBC) or mixture of both. Both of these have suppressive activity against C. gloeosporioides of papaya and could be used as enhancer for biocontrol efficacy of strain B34 during fruits storage. The survival and proliferation of strain B34 in papaya wounds and on fruit surfaces was not affected by aloe gel and SBC throughout the storage period. In addition, as observed from scanning electron microscopy micrograms, strain B34 was able to colonize and multiply on the surface of papaya fruits. The combination of strain B34 with aloe gel and SBC was more effective in controlling the anthracnose disease than strain B34 alone or other treatments, even superior to that obtained with fungicide Benocide® (benomyl 50% WP) both in inoculated or naturally infected fruits stored at 12±1ºC and 90±5% RH for 18 and 14 days, respectively. However, this combination offered a greater control by reducing 98.2% of the disease over control in naturally infected fruits at the end of 14 days storage at 12±1ºC and 90±5% RH and six days post ripening at 28 ± 2ºC,which was superior to that found with Benocide® or other treatments tested. Furthermore, fruits treated with the combination of B. subtilis-aloe gel-SBC showed delayed climacteric respiration and ethylene evolution more than seven days compared to control with reduced rate of CO2 and C2H4 productions. This combined treatment reduced weight loss by more than 25% compared to the control. It also markedly slowed down the ripening of fruits as shown by their retention of firmness after storage. Moreover, it also delayed changes in external colour, titratable acidity and pH without compromising fruit quality was observed in fruits that were subjected to the combined treatment. The storage life was thus extended by 15 days when compared with control. Inhibitory activity of strain B34 preserved in glycerol was also observed in this study. strain B34 preserved in 2% glycerol based liquid formulations showed economically better performance in terms of controlling C. gloeosporioides and number of viable propagules (CFUs) over 120 days of test period. Finally, it is clear that strain B34 not only able to store at 2% glycerol for longer time but also effective when incorporated with SBC and Aloe vera gel to control C. gloeosporioides as well as improve the postharvest quality during cold storage compared to Benocide®. This suggested that this composite coating is promising and eco-friendly to be used in commercial postharvest applications for prolonging the storage life of Frangi papaya.